PECULIARITIES OF FORMING POSITIVE IMAGE OF THE NATIONAL GUARD OF UKRAINE MILITARY UNITS AT SITES OF PERMANENT DEPLOYMENT - Tovma, Mykola; Turchinov, Artem (Honor and Law, 2022)
The article describes the peculiarities of forming a positive image of the National Guard of Ukraine military units in sites of permanent deployment. The study made it possible to identify factors influencing the formation of a positive image of the National Guard of Ukraine military units in sites of permanent deployment. During transformation of the modern Ukrainian society, the successful solution of the problems of strengthening the defense capability of our state is inevitably connected with the need to develop a positive image of the military man and the National Guard of Ukraine in general in order to increase the attractiveness of military service. The level of moral state, the moral and psychological state of the military men and the desire of young people to perform military service depends on the available positive image of the National Guard of Ukraine. The purposeful and systematic formation of a positive image has become especially relevant today. Many researchers are interested in identifying the main factors that influence the formation of a positive image of the National Guard of Ukraine. The analysis of scientific researches shows that there are definitions of military image functions, but there are no common approaches to identify the system of factors that positively affects the image of the National Guard of Ukraine. The study shows that the main purpose of forming the National Guard of Ukraine image is to increase positive public opinion about it. It is found out that factors that influence the formation of a positive image of the National Guard of Ukraine military units in the places of constant location are: official policy of the state in the fields of defense; informational policy and propaganda activities of the state in the promotion of military service; corporate culture of military men; advertising and PR activities of military structures; communicational skills of the personnel with the citizens. Concerning personal qualities of the servicemen which positively impact the image of the National Guard of Ukraine as a whole the following activities have been outlined: the development of high level of servicemen’s accountability for personal actions and results of their activities; development of the servicemen’s potential intellect; enhancing the moral and ethical requirements for the candidates for military service in the National Guard of Ukraine; enhancing the level of cultural training of the personnel.